?SYNTHESIS OF HETERO-BICYCLIC COMPOUNDS Part-IX. Formation of 2,2-disubstituted 4,5-dioxo-pyridino [4,3-d] [1,3]dioxins - Butt, M.A.; KEMAL, R.; SALAM, A.; AKHTAR, A (Biological Sciences - PJSIR, 1997)
Chloropyranodioxins (I) prepared by the reaction of malonyl chloride with mixed ketone were converted into 7- (phenylamino)-pyranodioxins (II) which underwent the phenoxide rearrangement to yield the corresponding pyridinodioxins (III), whose structures were determined by chemical conversions and spectroscopic studies.